2018
DOI: 10.1371/journal.pone.0194906
|View full text |Cite|
|
Sign up to set email alerts
|

What matters to women during childbirth: A systematic qualitative review

Abstract: IntroductionDesign and provision of good quality maternity care should incorporate what matters to childbearing women. This qualitative systematic review was undertaken to inform WHO intrapartum guidelines.MethodsUsing a pre-determined search strategy, we searched Medline, CINAHL, PsycINFO, AMED, EMBASE, LILACS, AJOL, and reference lists of eligible studies published 1996-August 2016 (updated to January 2018), reporting qualitative data on womens’ childbirth beliefs, expectations, and values. Studies including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
280
0
22

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 348 publications
(325 citation statements)
references
References 46 publications
23
280
0
22
Order By: Relevance
“…The synthesis of evidence supporting the development of the 2018 WHO recommendations on intrapartum care showed that women want a ‘positive childbirth experience’ that fulfils or exceeds their prior personal and sociocultural beliefs and expectations 5, 15. This includes giving birth to a healthy baby in a clinically and psychologically safe environment, with continuous emotional support from a birth companion and technically competent clinical staff.…”
Section: The Who Intrapartum Care Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of evidence supporting the development of the 2018 WHO recommendations on intrapartum care showed that women want a ‘positive childbirth experience’ that fulfils or exceeds their prior personal and sociocultural beliefs and expectations 5, 15. This includes giving birth to a healthy baby in a clinically and psychologically safe environment, with continuous emotional support from a birth companion and technically competent clinical staff.…”
Section: The Who Intrapartum Care Modelmentioning
confidence: 99%
“…The synthesis of evidence supporting the development of the 2018 WHO recommendations on intrapartum care showed that women want a 'positive childbirth experience' that fulfils or exceeds their prior personal and sociocultural beliefs and expectations. 5,15 This includes giving birth to a healthy baby in a clinically and psychologically safe environment, with continuous emotional support from a birth companion and technically competent clinical staff. The concept was informed by the evidence that most women want a physiological labour and birth, and to have a sense of personal achievement and control through their involvement in decision making, even when medical interventions are needed or wanted.…”
Section: Why Do We Need To Revisit Intrapartum Care?mentioning
confidence: 99%
“…The training content was based on evidence-based practices on the management of the complications and recommended practices known to have positive effects on birth outcomes and women's experiences such as support and mobility during labor and nonsupine position at delivery. 3,[20][21][22][23][24][25] In addition, simulation scripts had prompts for certain behaviors from the patient actress: For example, if providers did not introduce themselves, the patient actress asked "who are you? ", and if providers did not explain what they were doing or found from examinations, she asked "what are you doing to me?"…”
Section: Study Site and Interventionmentioning
confidence: 99%
“…In high‐income countries, research confirms the effectiveness of midwifery care, and in low‐ and middle‐income countries, midwives have played a critical role in reducing maternal and perinatal mortality and morbidity . Investigators have documented women's desire for a positive birth experience that includes birthing a healthy newborn in an environment that is both clinically and psychologically safe, supported by competent and kind professionals . These findings are in line with recent guidance from the World Health Organization, which notes that, for many women, birth is about more than mere survival …”
Section: Introductionmentioning
confidence: 53%
“…Midwifery education can, and should, provide expertise and leadership to meet these challenges. Essentially, midwifery education is responsible for molding students into professionals who meet the needs of women for positive birth
✦Increasing student midwife agency as advocates of physiologic birth is an important component of midwifery education. ✦Specific educational initiatives can be designed using rapid prototyping methodology, which includes the views and feedback of important stakeholders. ✦A focus on communication skills such as discussion and debate may increase student midwife agency as guardians of physiologic birth. ✦The Optimality Index is a useful tool that can be used to structure evidence‐based reflection by student midwives on their own care processes.
experiences that are as physiologic as possible while navigating the challenges presented by medicalization. This requires the development and internalization of an attitude that reflects the midwifery ethos of physiologic birth .…”
Section: Introductionmentioning
confidence: 99%